Cowpea as an intercrop under cereals - Wien, H.C.; Nangju, D. (1976)
One of the commonest systems involves grain legumes such as cowpea or groundnut planted under cereals such as sorghum, millet, or maize (31). Steele (32) suggests that cowpea may have come from its supposed center of origin, Ethiopia, to the West African semi-arid zone as part of such a cereal-legume farming system.